Experimental characterization of a novel ventilation system for multi-story buildings with continuous curtain walls. (15th September 2021) - Fascetti, Alessandro; Palladino, Alessandro
Abstract : Purpose: The purpose of this paper is to present the results of an experimental campaign conducted on a recently developed fire protection system (FPS), specifically designed for installation on continuous glass curtain walls systems typical of multi-story buildings. Design/methodology/approach: The authors will first present the theoretical derivation of the relevant parameters to characterize and predict the fire evolution and probability of flashover, according to existing codes and standards. Then, the results of two full-scale tests will be presented in terms of temperature fields, thermal gradients and position of the neutral plane. Findings: The experimental evidence shows how the proposed system is able to dramatically reduce internal temperatures in the rooms interested by the fire, also allowing for safer evacuation procedures by increasing the height of the neutral plane. Originality/value: The novel window frame element comprises an automatic doubly convergent aperture system that induces ventilation in the compartment by increasing internal convection in the rooms subject to the fire. This allows for an efficient dispersion of hot gases and fumes and a drastic improvement in safety for both the occupants and firefighting operators. The theoretical results are then compared to the experimental evidence to evaluate the performance of the proposed ventilation system in the context of existing standards and design procedures.